Post-ICU Treatment Experiences of Patients with Functional Disabilities - Silva, Camila Zucato da; Campos , Claudinei José Gomes; Jamarim , Michelle Ferraz Martins; Lima, Gerusa Marcondes Pimentel de Abreu (Revista Cuidarte, 2020)
Introduction: Understanding the experiences of patients with functional disabilities after Intensive Care Unit treatment following their return home. Materials and methods: A qualitative study was conducted using the case study as a research method. The sample of eight participants was intentionally composed and closed by theoretical saturation. Data was collected through semi-structured home interviews supplemented by field notes and diaries. Collected data were analyzed using the thematic content analysis proposed by Minayo. Results: Primary care, through home care, was the main responsible for the post-discharge follow-up of participants. From the empirical material, the categories "emotional distress and its impact on functional recovery" and "loss of family role and conflicts with caregivers" were created. Discussion and conclusions: Functional recovery of patients with functional disabilities after going through intensive care can be complex that, besides physical rehabilitation, adequate psycho-emotional monitoring, requires clarification of memories of hospitalization and professional support to the family. It is suggested that primary care staff receive training on the complexity of these patients and the creation of strategies that bring them closer to inpatient care, thus allowing shared and continuous care. How to cite this article: Silva, Camila Zucato; Campos, Claudinei José Gomes; Jamarim, Michelle Ferraz Martins; Lima, Gerusa Marcondes Pimentel de Abreu. Vivências de pacientes diante de incapacidades funcionais pós-tratamento em Unidade de Terapia Intensiva. Revista Cuidarte. 2020; 11(2): e1018. http://dx.doi.org/10.15649/cuidarte.1018